Effect of Purified prodigiosin from Serratia Marcescens on the Inhibition of Breast Cancer (MCF-7 and CAL-51 Cell Line) - Taif H. Hassan1 , Sawsan H. Authaman1 , Khawlah J. Khalaf1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The prodigiosin pigment was extracted from Serratia marcescens bacteria by using different methods such as by using ethyl acetate and acetone and purified by using column cahromatography , Detection and characterization of the pigment was done by using Thin layer chromatography and ? max, The purified Prodigiosin was dissolved in DMSO solvent and prepared in four concentration (1000, 500, 250, 125) µg/ ml at exposure time 24 hrs so it was used in treating MCF7 and CAL-51 cell line, the result showed that the inhibition ratio against MCF-7 was significant (p < 0.001) and maximum ratio of inhibition was 83% at conc. of 1000 µg/ml , 78% at 500 µg/ml , 73% at 250 µg/ml and 72% at 125 µg/ml while inhibition ratio against CAL-51 was also significant (p < 0.001) and 78% inhibition ratio was seen at conc. of 1000 µg/ml , 61% at 500 µg/ml , 27% at 250 µg/ml and 14% at 125 µg/ml , effect of the solvent DMSO on tumor cells also was studied and compared to the effect of prodigiosin and result showed that there was no effect or slightly effect of the solvent DMSO on MCF-7 tumor cells.(Inhibition was 6% ,13% ,16% , 22% for conc. 125 , 250 , 500 , 1000 µg/ml respectively) also there was no effect or slightly effect of the solvent DMSO on tumor CAL-51 cells.(Inhibition was 2% , 8% , 21% , 26% for conc. 125 ,250,500, 1000 µg/ml respectively) .